Identification of peroxiredoxin 6 as a direct target of withangulatin A by quantitative chemical proteomics in non-small cell lung cancer - Chen, Chen; Gong, Lijie; Liu, Xiaoqin; Zhu, Tianyu; Zhou, Wuxi; Kong, Lingyi; Luo, Jianguang (Redox biology, 2021)
Peroxiredoxin 6 (PRDX6), as a bifunctional enzyme with glutathione peroxidase activity (GPx) and Ca2+-independent phospholipase A2 (iPLA2) activity, has a higher expression in various cancer cells, which leads to the increase of antioxidant properties and promotes tumorigenesis. However, only a few inhibitors of PRDX6 have been discovered to date, especially the covalent inhibitors of PRDX6. Here, we firstly identified Withangulatin A (WA), a natural small molecule, as a novel covalent inhibitor of PRDX6. SILAC-ABPP identified that WA could directly bind to PRDX6 and inactivate the enzyme activity of PRDX6 by the α, β-unsaturated ketone moiety. Moreover, WA also facilitated the generation of ROS, and inhibited the GPx and iPLA2 activities. However, WA-1, with a reduced α, β-unsaturated ketone moiety, had no significant inhibition of the GPx and iPLA2 activities. Biolayer interferometry and LC-MS/MS analysis further demonstrated the selectively covalent binding of WA to the cysteine 47 residue (Cys47) of PRDX6, while mutation of Cys47 blocked the binding of WA to PRDX6. Notably, WA-mediated cytotoxicity and inhibition of the GPx and iPLA2 activities were almost abolished by the deficiency of PRDX6. Therefore, this study indicates that WA is a novel PRDX6 covalent inhibitor, which could covalently bind to the Cys47 of PRDX6 and holds great potential in developing anti-tumor agents for targeting PRDX6. [Display omitted] •Withangulatin A is a novel covalent inhibitor of PRDX6.•Withangulatin A inhibits the activity of PRDX6 and increased the generation of ROS.•Withangulatin A inhibits the GPx and iPLA2 activities.•Withangulatin A selective covalently binds to the Cys47 of PRDX6.•Withangulatin A-mediated cytotoxicity and generation of ROS are dependent on PRDX6.